A Comparative Analysis of Patent Laws in Afghanistan and the TRIPS Agreement - Parsa Manush, Mir Ahmad; Mujadidi, Sayed Abdul Talib (CV. AFDIFAL MAJU BERKAH, 2024)
The Agreement on Trade-Related Aspects of Intellectual Property Rights provides for a minimum standard of Intellectual protection. All WTO member countries are under an obligation to comply with the provision of provisions Agreement. Afghanistan, as a member of the WTO, in the case of intellectual property rights, committed to full implementation of the provision of the TRIPS Agreement. Hence, is required to coordinate all its trade law, including patent law. This research paper examines Afghanistan's patent regime in relation to the RTIPs Agreement. The paper provides a comprehensive overview of the fundamental concept of patents and the historical background of patents in the legal system of Afghanistan. It then delves into an analysis of the law and regulations in Afghanistan, evaluating their compliance with the TRIPs agreement. The findings of this research indicate that Afghanistan patent law is compatible with the minimum standard of patent protection in the TRIPs Agreement. Nevertheless, Afghanistan’s patent law is insufficient, there are certain legal lacuna in its provisions which must be amended.